Tobacco smoking as a potential risk factor for pulmonary tubercolosis A meta-analysis - Chipeta, John, Benson. (My University, 2001)
Objective. The aim of this paper was to systematically evaluate available evidence on tobacco smoking as a risk factor for pulmonary tuberculosis. Methods. Relevant reports were identified by a systematic electronic search of Medline, Pubmed, Nioshtic, Toxline and Embasse. Methodological quality of all selected publications was assessed using a standardized checklist. Information was collected on all major study characteristics. Inter-study heterogeneity was examined qualitatively and statistically using the DerSimonian and Laird method. Results. Five case-control studies and 1 cohort study were included in the systematic review. All the 6 studies revealed a relationship between tobacco smoking and pulmonary tuberculosis. Heterogeneity across studies hampered overall statistical pooling of results, however pooled risk ratios for sub-groups were determined
A research report submitted to the Faculty of Heath Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Medicine in the field of Tropical Diseases (Epidemiology & Biostatistics) Johannesburg,
Keywords: Tobacco Smoking; Tuberculosis, Pulmonary; HIV